Treatment of polluted water (river) by using activated carbon from coir pith - Amryana, Pohan (2010)
Coconut coir pith waste is a highly porous by product generated during separation of coconut fibers from its shell. Its accumulation in fiber production units causes problem of disposal and environmental pollution. Due to its highly porous structure and fixed carbon content, it has been tried as a raw material for the production of activated carbon (AC). A physical activation method has been implemented to produce activated carbon from cleaned coconut coir pith. The coir pith has been put in the small porcelain with lid and burned in the furnace with temperature range of 500"C for 2 hours. The activated carbon then impregnated with acid sulphuric and distilled water to balance the pH value. The AC divided into two sizes which is Granular Activated Carbon (GAC) and Powdered Activated Carbon (PAC). AC was characterized with SEM and particle size analysis. The SEM pictures of activated carbon particles showed enlargement of pore volume. The polluted water was taken from Sg Galing, Kuantan and all eleven parameters has been tested which are pH, turbidity, Total Coliform, Total Dissolve Solids, COD, BOD 5, Total Suspended Solid, iron, zinc, chromium and cuprum. All the parameters were compared with Malaysia Drinking Water Quality Standard. Sg Galing treated with GAC and PAC show decrement in iron, zinc, chromium and cuprum concentration. According to Malaysia Standard, the water is safe to be used for drinking.